More Sugar, Less Salt: Edith Hancox and the Passionate Mobilization of the Dispossessed, 1919–1928 - Thompson, David (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2020)
A champion of impoverished women, children, immigrants, and the unemployed, Edith Hancox’s chosen family were capital’s dispossessed. Rosemary Hennessy’s material feminist theory of affect-culture and Antonio Gramsci’s articulation of the impassioned organic intellectual offer a conceptual framework for the emotive role Hancox played in nurturing and sustaining working-class resistance in the aftermath of the Winnipeg General Strike. A partial biography is gleaned from contemporary newspaper reports, Hancox’s journalism, government records, family correspondence, and other archival sources. What emerges is a glimpse into the actions, thoughts, and lived experiences of a profoundly significant, yet neglected, socialist feminist. An illegitimate birth, servitude, marriage, motherhood, immigration, and a critical engagement with organized religion formed the basis of Hancox’s radical leadership during the Winnipeg revolt. As secretary of the first national unemployment association in Canada, Hancox mobilized thousands of the nation’s workless and presented a devastating gender, race, and class critique of liberal capitalism. Through her writing and activism, she also challenged the most important leftist organizations of her era – the Labor Church, the Women’s Labor League, the One Big Union, and the Communist Party of Canada – to build a more expansive and inclusive revolutionary movement.